Monument Restoration Practices in Southeast Asia and the Angkor Charter - Petre Lucian VLAD (ACROSS)
The restoration of historic monuments in particular geographic regions differs in both theory and practice. In order to implement such projects, it is necessary to understand the context of their original build, their cultural significance, and apply scientifically proven methods which may require the experience and research of foreign specialists and international specialized organisations. Major projects may also become the basis of new research and practices, benefitting from transboundary and interdisciplinary collaborations. Spanning more than a century of conservation practice, the Angkor Wat temple complex has inspired numerous studies in the fields of history, archaeology, conservation and restoration. The Angkor Charter aims to collect this experience and synthesize it into a series of guidelines for the benefit of cultural heritage, which has inspired work in this field for more than a decade now.